2019
DOI: 10.3892/ol.2019.11078
|View full text |Cite
|
Sign up to set email alerts
|

Significant function and research progress of biomarkers in gastric cancer (Review)

Abstract: Gastric cancer is one of the most common gastrointestinal tumor types, and the incidence and mortality rates are higher in men compared with women. Various studies have revealed that gastric cancer is a spectrum of tumor types, which have biological and genetic diversity. It has proven to be difficult to improve the overall survival and disease-free survival of patients with gastric cancer through the use of traditional surgery and chemoradiation, as gastric cancer is usually identified at an advanced stage. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 152 publications
(174 reference statements)
0
21
0
Order By: Relevance
“…Gastric cancer is the fifth most common cancer and the third most common cause of cancer-related death on a global scale [ 1 ]. Due to the nature of gastric cancer, diagnosis is often made late in the disease course, such that many patients miss the best time for treatment [ 2 ]. Due to the usually late diagnosis, lymphatic metastasis and distant metastasis are the leading causes of death of gastric cancer patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is the fifth most common cancer and the third most common cause of cancer-related death on a global scale [ 1 ]. Due to the nature of gastric cancer, diagnosis is often made late in the disease course, such that many patients miss the best time for treatment [ 2 ]. Due to the usually late diagnosis, lymphatic metastasis and distant metastasis are the leading causes of death of gastric cancer patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the correlation analysis between clinical indicators and gastric cancer risk, we also found that the ZBTB20 polymorphic site rs9841504 and platelet showed a certain significant correlation ( P =0.048). Platelet involves in cancer growth and metastasis is a long-term concept [ 41 ], and studies have shown that the ratio of platelet to lymphocyte and CA242 may be convenient biomarkers for gastric cancer prognosis [ 42 , 43 ]. Therefore, our results suggested that rs9841504 may play a certain role in the influence of platelets on the occurrence and development of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is globally ranked third among the causes of cancer-related death, and the majority of cases are discovered at the late stage, with almost half of the recorded cases from East Asian countries, such as China, Japan, and South Korea [ 99 , 100 ]. A report showed that PPD including 25-hydroxyprotopanaxadiol (25-OH-PPD) and 25-methoxylprotopanaxadiol (25-OCH3-PPD) had potent anti-tumor properties, such as cell growth inhibition and apoptosis induction in gastric cancer cells lines [ 101 ].…”
Section: Gastric Cancermentioning
confidence: 99%